The B side of imagination. Hume on imperfect ideas - Calvente, Sofía Beatriz (Belgrade Philosophical Annual.)
My aim is to look into the representational aspect of ideas, exploring not only to what Hume refers as adequate ideas, but also these cases where for a number of reasons an idea does not reach that standard. It has been suggested that the latter are fictions, but an in-depth examination of Hume texts reveals that there are several types of imperfections, such as incompleteness or imprecision that prevent an idea from being adequate. This leads to an analysis of the status of supposed or pretended ideas, and the possibility of there being terms with no ideas annexed to them.